Efficacy of onabotulinumtoxinA treatment in episodic migraine - Jasem Al-Hashel; Jasem Al-Hashel; Raed Alroughani; Malak Almojel; Malak Almojel; Samar Farouk Ahmed; Samar Farouk Ahmed (Frontiers in Neurology)
BackgroundOnabotulinumtoxinA (BoNT-A) is approved as a prophylactic treatment of chronic migraine (CM) only. We aimed to assess the efficacy and safety of BoNT-A in the treatment of episodic migraine (EM).MethodsThis is a prospective study included migraine patients, aged 18–65 years, and completed 1 year treatment with BoNT-A. Patients received 4 courses of BoNT-A treatment. Patient’s headache was assessed by headache diary at baseline, and before every injection. Migraine Specific Quality of Life Questionnaire (MSQ) and work productivity were collected at baseline and in their last visit. Adverse events (AEs) were reported.ResultsThe study recruited 210 patients. Between baseline and the final visit, there were a significant reduction in migraine days, analgesic consumption days, and headache severity (9.54 ± 1.70 versus 4.58 ± 2.77, p < 0.001), (8.47 ± 1.49 versus 2.98 ± 0.21, p < 0.001), (8.37 ± 0.72 versus 2.54 ± 0.18, p < 0.001), respectively. BoNT-A treatment reduced the mean number of missed hours from work and daily activities over a 7-day period (4.63 ± 2.39 versus 6.26 ± 2.04, p < 0.001); (2.24 ± 3.30 versus 3.94 ± 3. 45; p < 0.001). Treatment with BoNT-A significantly improved the MSQ scores at last visit versus baseline visit, MSQ Role Function-Restrictive (51.55 ± 29.12 vs. 26.89 ± 17.42; p < 0.001), MSQ Role Function-Preventive (56.07 ± 24.73 vs. 30.64 ± 15.25; p < 0.001), and for MSQ Emotional Function (76.47 ± 115.29 vs. 35.12 ± 20.83; p < 0.001). Fifty-four patients (14.4%) experienced mild and short-lasting AEs.ConclusionBoNT-A is an effective and well tolerated therapy in the prophylaxis of EM. It improved MSQ and WPAI.